SYIAH DAN POLITIK: STUDI REPUBLIK ISLAM IRAN - Kadir, Abd. (JPP (Jurnal Politik Profetik), 2015)
This article reviews the relation between Shi’ah and politics in its real form and structure within political system and governance. Iran represents a government in which Shi’ah has been its political ideology, particularly after the Islamic Revolution of Iran in 1979 and this in turn makes Iran as a country under clerical rule or system of Wilayatul Faqih with Ayatollah Khomeini as its first supreme leader. 1979 Revolution created the momentum for the teachings of the Shi’ah sect influencing social structure and governance of the Iranian nation and replaced the Iranian monarchy that has survived for 25 centuries. Shia’h sect showed its influence by becoming the basis of ideology and of social and political system of Iran.